Imprisonment for international crimes: an interdisciplinary analysis of the ICTY sentence enforcement practice - Vojta, Filip (Research series of the Max Planck Institute for Foreign and International Criminal Law Publications of the Max Planck Partner Group for Balkan Criminology, 2020)
How criminal sentences are enforced, is of fundamental concern for the legitimacy of any justice system. However, fairly little is known about the practice of enforcing the prison sentences imposed by the international criminal tribunals. This volume offers a unique interdisciplinary lens – including international criminal and human rights law, penology, (supranational) criminology, transitional justice and terrorism studies – through which the policy and practice of enforcing the sentences of the International Criminal Tribunal for the former Yugoslavia (ICTY) are analyzed. It is the first scientific work to comprehensively explore the significance of penal rehabilitation for the perpetrators of international crimes and its implementation in the prison treatment of the ICTY convicts. The analysis is informed by rich and systematically collected empirical data, including in-depth interviews with the ICTY/MICT officials, national prison officials, imprisoned ICTY convicts and released ex-prisoners. It shows comparatively – and in previously unseen detail – the trials and tribulations the practice of enforcing the ICTY sentences in different European prisons faces and offers necessary recommendations for the improvement of the vertical system for enforcement of international sentences.